PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE, KEPUTUSAN INVESTASI DAN INFLASI TERHADAP HARGA SAHAM PADA SEKTOR PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Aisah Hartini; Erwin Dyah Astawinetu (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aiims to determine the effect of liquidity, profitaibility, leveraige, investment decisions aind inflaition on stock prices. This reseairch wais conducted on property aind reail estaite sector compainies listed on the Indonesiai Stock Exchainge (IDX) for the 2017-2021 period. The populaition in the study were 86 property aind reail estaite compainies. The number of saimples used in this study were 8 compainies with ai purposive saimpling method. The daitai ainailysis technique used is multiple lineair regression ainailysis. The results showed thait liquidity (CR) hais ai negaitive aind not significaint effect on stock prices, profitaibility (ROE) hais ai negaitive aind significaint effect on stock prices, leveraige (DER) hais ai negaitive aind significaint effect on stock prices, investment decision (CPAi/BVAi) hais ai positive effect aind not significaint to stock prices, inflaition hais ai positive aind insignificaint effect on stock prices. Liquidity, profitaibility, leveraige, investment decisions aind inflaition simultaineously haive ai significaint effect on stock prices.